Performance Evaluation of AODV and DSR Routing Protocols with PCM and GSM Voice Encoding Schemes - Fadhil, Osamah Yaseen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
A mobile ad hoc network (MANET) is one of the narrowest and most specific of research topics in the field of telecommunications. The growth of this type of network, and the large number of applications with mobility requirements, has led to a wider study and research in the analysis and enhancement of the work in this area. In such networks, nodes are communicating with each other without the need of a centralized administration (This type of network does not contain any type of server or base station). In this topology, the communication between the nodes is done by pair to pair within the coverage area. The routing is managed and organized by a number of routing protocols. A limited coverage area, collision and power consumption for mobile nodes are the main problems occurring in such networks. In this thesis, two important MANET routing protocols were used, AODV and DSR to analyze their behavior with two different voice encoding schemes, Pulse Code Modulation (PCM) and Global System Mobile (GSM). The PCM and the GSM encoding voice schemes are evaluated with a different number of clients using a Random Way Point Mobility (RWPM) model. OPNET simulator version 17.1 was used to build the modeler and to simulate the ad hoc mobile network model. The benefit of this simulation program is the ability to build models for different network topologies and the large number of available choices for node performance statistics. In addition to that, results are more confident and accurate compared to other simulation programs found in the literature. From the analysis of the simulations, it was concluded that, in all cases, the AODV protocol performed better than the DSR protocol. This is because AODV doesn’t save the entire possible path from source to the destination node. It takes the newest and most refreshable one. On the other hand, DSR caches all possible paths to the destination. It is also shown that PCM performance is better and more quality than GSM in most of the performance metrics except end -to- end delay, for both AODV and DSR routing protocols. Keywords: OPNET simulator, Mobile Wireless Ad Hoc Network, AODV, DSR, PCM, GSM.

ÖZ: Mobil özel amaca yönelik ağ (MANET) telekomünikasyon alanında en dar ve özel araştırma konularından bir tanesidir. Son yıllarda, bu tür ağların kullanımında ve hareket gerektiren uygulamaların sayısında artış yaşanmıştır. Bu durum da ilgili alanda daha geniş çalışma ve araştırmaların yapılmasına yol açmıştır. Bu ağlarda, düğümler (node) merkezi bir yönetime ihtiyaç duymadan birbirleri ile iletişim kurabilmektedirler. Bu tür ağlar, herhangi bir sunucu ya da baz istasyonu içermemektedir. Bu topolojide, iletişim, kapsama alanı içindeki düğümler tarafından çiftli yapılmaktadır. Yönlendirme, bir dizi yönlendirme protokolleri tarafından yönetilmekte ve organize edilmektedir. Mobil düğümler için, sınırlı bir kapsama alanı, çarpışma ve güç tüketimi bu tür ağlarda meydana gelen başlıca sorunlardır. Bu tez çalışmasında, iki önemli MANET yönlendirme protokolü olan AODV ve DSR’nin iki ayrı ses kodlama şeması Darbe Kod Modülasyonu (PCM) ve Küresel Sistem Mobil (GSM)’deki davranışları analiz edilmeye çalışılmıştır. PCM ve GSM kodlama ses şemaları, farklı istemci(client) sayıları ile bir Random Way Point Mobility (RWPM) model kullanılarak değerlendirilmiştir. OPNET simülatörü 17.1 sürümü modelleyici inşa etmek ve ad hoc mobil ağ modelini simüle etmek için kullanılmıştır. Bu simülasyon programının yararı, farklı ağ topolojileri ve çok sayıda kullanılabilir mevcut düğüm performans istatistikleri için, modelleri inşa etme yeteneğinin olmasıdır. Buna ek olarak, sonuçlar literatürde bulunan diğer simülasyon programları ile karşılaştırıldığında daha güvenli ve doğru olduğu tespit edilmiştir. Gerçekleştirilen simülasyonları analizlerinden, AODV protokolünün her durumda, DSR protokolden daha iyi performans sağladığı sonucuna varılmıştır. Çünkü AODV kaynaktan hedefe, gidilecek düğüme ulaşmak için olası yolların tümünü kaydetmemektedir. AODV, olabilecek en yeni ve en yenilenebilir yolu almaktadır. Diğer taraftan DSR, hedefe ulaşmak için mümkün olan tüm yolları önbelleğine almakta, buda daha fazla çarpışmaya ve gecikmeye neden olmaktadır. Ayrıca bu çalışma, PCM performansının, performans ölçümlerinin çoğunda, uçtan uca gecikme hariç, AODV ve DSR yönlendirme protokollerinin her ikisi içinde daha iyi ve daha kaliteli olduğunu göstermiştir. Anahtar Kelimeler: OPNET simulatörü, Mobil kablosuz özel amaca yönelik ağlar, AODV, DSR, PCM, GSM
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Internetworking (Telecommunication); Computer network protocols; Ad hoc networks (Computer networks); OPNET simulator; Mobile Wireless Ad Hoc Network; AODV; DSR; PCM; GSM